Категория интертекстуальности в комическом институциональном дискурсе - Лобова, О.К.; Lobova, O.K. (Харкiвський нацiональний унiверситет iм. В.Н. Каразiна, 2014)
Статья посвящена исследованию интертекстуальности как одной из основных категорий комического институционального дискурса. Категория интертекстуальности актуализируется использованием стэндап-комиками имен собственных и феноменов, которые репрезентируются немаркированными интекстами (цитатами, аллюзиями и реминисценциями), а также приемом стилизации. Стаття присвячена дослідженню інтертекстуальності як однієї з базових категорій комічного інституційного дискурсу. Категорія інтертекстуальності актуалізується залученням стендап-коміками власних назв та феноменів, що репрезентовані немаркованими інтекстами (цитатами, алюзіями та ремінісценціями), а також прийомом стилізації. The article deals with the investigation of intertextuality as one of the main categories of comic institutional discourse. The category of intertextuality is actualized by standup-comedians by using proper names and phenomena, which are represented with non-marked intexts (citation, intimations, reminiscences) and also stylization.
The category of intertextuality in comic institutional discourse
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science; Research Subject Categories::SOCIAL SCIENCES::Social sciences::Education; Research Subject Categories::HUMANITIES and RELIGION::Languages and linguistics; category; citation; discourse; intimation; intertextuality; reminiscence; аллюзия; дискурс; интертекстуальность; категория; реминисценция; цитата